WEB-Based Empowerment of Individuals to Detect Health Status and Follow-Up Treatment - Ariga, Reni Asmara; Ikhsan, Edy; Nurbaiti; Ariga, Selviani; Ariga, Fajar Amanah; Astuti, Sri Budi; Ariga, Hijrah Purnama Sari; Sari, Dian Maya (Talenta Publisher, 2024)
The high morbidity and mortality rate of the community is due to lack of knowledge in detecting health status and inability to make decisions to overcome health problems, causing delays in treatment. Providing education in the form of simulations and applying patents of a method of increasing independence for detecting health status and following up on appropriate treatment and patents of WEB site-based self-care methods is the application of information and communication technology in nursing services which is one solution to overcome this because it can optimize individual independence so that distance, time, place, and cost are not an obstacle to getting nursing services and achieving SDGs 3; ensuring a healthy life and improving the welfare of the population. Community service uses interview methods, health promotion about upper respiratory tract infections, hypertension, infections, rheumatism, dental caries, skin infections, refractive errors, pulmonary tuberculosis, pulp and pariapical tissue diseases and cataracts. Followed by simulations, assistance to all participants in using the WEB https://ariganursingselfcare.com/, observation and monitoring of the application of WEB to increase independence in detecting health status and following up on treatment. Community service was carried out from August to October 2023 in the community in the Medan Sunggal Health Center working area with a total of 173 people. The results showed 113 (65%) respondents were independent in detecting health status and following up on treatment, but there were still 60 (35%) respondents who needed continuous assistance in applying the WEB.